Assessing the impact of COVID-19 on rural women and men in Uganda - Food and Agricultural Organization of the United Nations; United States Agency for International Development; International Food Policy Research Institute; Bryan, Elizabeth; Mawia, Harriet; Ringler, Claudia (Food and Agricultural Organization of the United Nations, 2021)
The first case of COVID-19 in Uganda was reported on March 22, 2020. The number of COVID-19 cases remained low during the first three quarters of 2020, before a first spike toward the end of the year. To understand the gendered impacts of the pandemic, phone surveys with rural women and men in Uganda were conducted. Data were collected from a sub-set of households drawn from a survey conducted in 2017 in 8 districts of the country: Iganga, Kasese, Kiboga, Luwero, Masaka, Masindi, Mbale, and Mubende. Four rounds of phone surveys were conducted in October 2020, February 2021, April 2021, and June 2021. The surveys focused on the economic impact, coping strategies, impact on food security and dietary diversity and the impact on children’s education and care burden. This brief presents the findings.